2008
DOI: 10.1111/j.1570-7458.2007.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional assessment of Helicoverpa zea populations on cotton and non‐cotton crop hosts

Abstract: Selection pressure on bollworm, Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae), by cotton, Gossypium hirsutum (L.) (Malvaceae), that produces one or more Bacillus thuringiensis Berliner (Bt) proteins is reduced by plantings of non‐Bt refuge cotton that produce non‐selected individuals. However, the contributions of non‐Bt, non‐cotton crop hosts to the overall effective refuge for H. zea on Bt cotton have not been estimated. A 2‐year, season‐long study was conducted in five US cotton‐producing states to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 33 publications
7
58
0
Order By: Relevance
“…Surveys of the major U.S. cotton pests, Heliothis virescens and Helicoverpa zea, indicate that both species utilize unstructured refuges at higher rates than we observed for ECB (Gould et al 2002, Gustafson et al 2006, Orth et al 2007, Jackson et al 2008. These data have played important roles in the 2007 approval by EPA to eliminate structured-refuge requirements in IRM plans for Bt cotton varieties pyramided with Cry1Ac and Cry2Ab2 genes in parts of the United States (EPA 2006a(EPA , 2008.…”
Section: Discussionmentioning
confidence: 54%
“…Surveys of the major U.S. cotton pests, Heliothis virescens and Helicoverpa zea, indicate that both species utilize unstructured refuges at higher rates than we observed for ECB (Gould et al 2002, Gustafson et al 2006, Orth et al 2007, Jackson et al 2008. These data have played important roles in the 2007 approval by EPA to eliminate structured-refuge requirements in IRM plans for Bt cotton varieties pyramided with Cry1Ac and Cry2Ab2 genes in parts of the United States (EPA 2006a(EPA , 2008.…”
Section: Discussionmentioning
confidence: 54%
“…Data (Neunzig 1964). Average captures from pheromone traps in both areas indicated that Ͼ90% of the heliothines were H. zea (Allen 2007 (Allen 2007, Jackson et al 2008 was being conducted at the interface of Bt cotton to understand heliothine movement among crops. Sampling began in early June and continued weekly through the Þrst week of September with four sets of 25 sweeps taken at random locations with a 38-cm sweep net in each soybean and cotton Þeld.…”
Section: Methodsmentioning
confidence: 99%
“…The natural refuge for resistance management of dual-toxin cottons, 41 is based largely on the production of bollworm from non-cotton hosts during the period of cotton susceptibility to infestations. Jackson et al 39 and Head et al 40 reported that most of the insects colonizing cotton were from C 4 hosts, probably corn. The threat of elevated resistance because of expanding acreages of Bt corn in cotton-growing regions is the impetus for research projects in the USDA, ARS Southern Insect Management Research Unit on the ecology, dispersal and resistance mechanisms of bollworm in these changing cotton-corn production systems.…”
Section: Target Lepidoptera Non-target Lepidoptera Non-target Non-lepmentioning
confidence: 98%
“…Efficient management of bollworm in cotton relies on Bt cotton, effective insecticides, and increasingly, a knowledge of landscape level information on pest population growth. 39,40 An important landscape level influence was the adoption of a natural refuge concept with the commercialization of pyramided-gene Bt multiple toxin cottons in 2002. 41 This change in EPA resistance management strategies for Bt previously controlled indirectly with broad spectrum insecticides targeted at boll weevil and tobacco budworm became more numerous and required control.…”
Section: Patterns Of Adoption Of Bt Technologymentioning
confidence: 99%
See 1 more Smart Citation